Comprehensive interrogation of synthetic lethality in the DNA damage response - John Fielden; Sebastian M. Siegner; Danielle N. Gallagher; Markus S. Schröder; Maria Rosaria Dello Stritto; Simon Lam; Lena Kobel; Moritz F. Schlapansky; Stephen P. Jackson; Petr Cejka; Marco Jost; Jacob E. Corn (Nature, 2025)
Abstract The DNA damage response (DDR) is a multifaceted network of pathways that preserves genome stability 1,2 . Unravelling the complementary interplay between these pathways remains a challenge 3,4 . Here we used CRISPR interference (CRISPRi) screening to comprehensively map the genetic interactions required for survival during normal human cell homeostasis across all core DDR genes. We captured known interactions and discovered myriad new connections that are available online. We defined the molecular mechanism of two of the strongest interactions. First, we found that WDR48 works with USP1 to restrain PCNA degradation in FEN1/LIG1-deficient cells. Second, we found that SMARCAL1 and FANCM directly unwind TA-rich DNA cruciforms, preventing catastrophic chromosome breakage by the ERCC1–ERCC4 complex. Our data yield fundamental insights into genome maintenance, provide a springboard for mechanistic investigations into new connections between DDR factors and pinpoint synthetic vulnerabilities that could be exploited in cancer therapy.